The hypoxia-inducible factor-1α in stemness and resistance to chemotherapy in gastric cancer: Future directions for therapeutic targeting - Ozcan, Gulnihal (Frontiers in Cell and Developmental Biology, 2023)
Hypoxia-inducible factor-1α (HIF-1α) is a crucial mediator of intra-tumoral heterogeneity, tumor progression, and unresponsiveness to therapy in tumors with hypoxia. Gastric tumors, one of the most aggressive tumors in the clinic, are highly enriched in hypoxic niches, and the degree of hypoxia is strongly correlated with poor survival in gastric cancer patients. Stemness and chemoresistance in gastric cancer are the two root causes of poor patient outcomes. Based on the pivotal role of HIF-1α in stemness and chemoresistance in gastric cancer, the interest in identifying critical molecular targets and strategies for surpassing the action of HIF-1α is expanding. Despite that, the understanding of HIF-1α induced signaling in gastric cancer is far from complete, and the development of efficacious HIF-1α inhibitors bears various challenges. Hence, here we review the molecular mechanisms by which HIF-1α signaling stimulates stemness and chemoresistance in gastric cancer, with the clinical efforts and challenges to translate anti-HIF-1α strategies into the clinic.